Impacto socio económico que ha producido el comercio informal en la ciudad de Machala. - Arias Morocho, Johanna Gabriela (My University, 2018)
The informal commerce since ancient times has been considered as a field of action, determined by the extreme competitiveness in the market, which generates a maximum commercial influx by the population, who are dedicated to this work, in order to maintain the daily support itself and that of the family. The present investigation is based on a study of informal commerce established in the main streets of the center of the city of Machala, such as Pasaje, Juan Montalvo, Sucre, Guayas and Olmedo, where a great index of informal commerce originates; having as objective, to analyze the impact that the informal merchants have produced before the inadequate use of the urban space of the central helmet of Machala. The methodology that was used to carry out this research is descriptive and explanatory, the same that were fulfilled by observation guides in the place where the merchants manifest themselves, in addition to conducting surveys aimed at informal traders who are located in the place, whose purpose is to know if this type of inadequate employment is favorable to them to maintain their daily sustenance in their homes. The results obtained were: The inadequate use of urban street space by informal traders; as also it was determined that the support provided by the municipal authorities to the informal traders of the central town of Machala, its stability is not guaranteed when the streets remain collapsed by the vehicles and people who circulate in this sector.
El comercio informal desde la antigüedad ha sido considerado como un campo de acción, determinado por la extremada competitividad en el mercado, que genera una máxima afluencia comercial por parte de la población, que se encuentran dedicados a esta labor, con la finalidad de mantener el sustento diario propio y el de la familia. La presente investigación se basa a un estudio del comercio informal establecido en las principales calles del centro de la ciudad de Machala, donde se da origen un gran índice de comercio informal; teniendo como objetivo, analizar el impacto que han producido los comerciantes informales ante la inadecuada utilización del espacio urbano del casco central de Machala. La metodología que se utilizó para la realización de esta investigación es de características descriptivas y explicativas, las mismas que se cumplieron mediante guías de observación en el lugar donde se manifiestan los comerciantes, además de la realización de encuestas dirigidas a los comerciantes informales que se localizan en el lugar, cuya finalidad es de conocer si este tipo de empleo inadecuado les es favorable para mantener su sustento diario en sus hogares. Los resultados obtenidos fueron: La inadecuada utilización del espacio urbano de las calles, por parte de los comerciantes informales; como también se determinó que el apoyo que brindan las autoridades municipales a los comerciantes informales del casco central de Machala, no se garantiza su estabilidad al permanecer las calles colapsadas por los vehículos y personas que circulan por este sector.
Keywords: COMERCIO INFORMAL; COMPETITIVIDAD; IMPACTO; AFLUENCIA